Individuality or Conformity? The Effect of Independent and Interdependent Self‐Concepts on Public Judgments - Torelli, Carlos J. (Journal of Consumer Psychology, 2006)
When both independent and interdependent self‐concepts are available, priming either self‐concept will increase the accessibility in memory of the motivations and cognitions associated with it. Thus, priming the interdependent self may activate motivation to maintain harmony and conform to others’ opinions, whereas priming the independent self is likely to activate motivation to be independent and to withstand social pressure. Two experiments investigated implications of these possibilities for judgments of risk when participants anticipated (or not) explaining their judgments to others. Participants relied on others’ beliefs only when their interdependent self was primed and they expected they might have to explain their judgments to others. When their independent self was primed, expectations to communicate theirjudgments had no effect. Culture‐based differences in individualism vs. collectivism had no impact on these effects.